The relationship between social class and subjective well-being: A serial mediation model - Hong, Youjuan; Wang, Xuemei; Liu, Liting; Su, Yankui; Chen, Lijun; Lian, Rong; Liao, Meiling (Frontiers in Psychology, 2022)
Despite recent research associating social class with subjective well-being (SWB), the relationship between the two, manifested through victim justice sensitivity and envy, has not been properly investigated. Guided by social comparison and social cognitive tendency theories, we explored the direct and indirect relationships between social class and SWB among Chinese undergraduate students. This study employed a cross-sectional, questionnaire-based research design. 1,405 undergraduate students completed questionnaires regarding subjective social class, victim justice sensitivity, envy, and SWB. The results showed that social class was positively related to SWB and negatively associated with victim justice sensitivity and envy. Victim justice sensitivity was negatively related to SWB, victim justice sensitivity was positively related to envy, and envy was negatively associated with SWB. Social class correlated with SWB through three paths: the mediating role of victim justice sensitivity, the mediating role of envy, and the serial mediating roles of victim justice sensitivity and envy. The results indicate that social class could contribute to college students’ SWB through the mechanisms of victim justice sensitivity and envy. This study advances the understanding of how the relationship between social class and college students’ SWB operates. Furthermore, the findings will facilitate the promotion of college students’ SWB.